Model of Sexual Education Based on Quranic Values within the Framework of Child Friendly Education in the Contemporary Era - Ali, Rahmadi; Saragih, Alkausar; Sakdiah, Khairani; Friska, Novita (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
Sexual crimes in schools can cause trauma to children and create discomfort in the educational environment. Therefore, sexual education for children is a preventive measure to protect them from violence and sexual deviance. This study aims to analyze the design of a Quran-based sexual education model implemented in children's educational institutions in Deli Serdang District, the management of a child-friendly educational environment that supports this model, and the challenges faced. This study uses a qualitative method based on phenomenological studies with data collection through interviews, observations, and document studies. The results of the study show five models that have been implemented, namely the Developmental-Based Sexual Education Model, the Qur'anic Literacy Sexual Education Model, the Family-Centered Sexual Education Model, the Community-Driven Sexual Education Model, and the Tech-Enhanced Sexual Education Model. Physical environment management involves providing safe spaces to prevent violence, while non-physical management focuses on a sensitivity-based approach. The greatest challenge faced is the difficult-to-control influence of technology. Implications of research on awareness to protect children from violence.